Competing for attention - Christopher Cotton (Queen's University, Department of Economics, 2015)
We develop a model of lobbying in which a time and resource constrained policymaker first chooses which policy proposals to learn about, before choosing which to implement. The policymaker reviews the proposals of the interest groups who provide the highest contributions. We study how policy outcomes and contributions depend on policymaker constraints and the design of the "Contest for Attention." Among other results, awarding attention to the highest contributors generally guarantees the first best policy outcome. It can also lead to the highest possible contributions, suggesting that a policymaker may not need to sacrifice policy in order to maximize contributions.
Keywords: D44; D78; D82; 330; all-pay auction; rent seeking; handicapped contest; political access; lobbying